2007
DOI: 10.1016/j.neuroimage.2006.10.012
|View full text |Cite
|
Sign up to set email alerts
|

The impact of processing load on emotion

Abstract: This event-related fMRI study examined the impact of processing load on the BOLD response to emotional expressions. Participants were presented with composite stimuli consisting of neutral and fearful faces upon which semi-transparent words were superimposed. This manipulation held stimulus-driven features constant across multiple levels of processing load. Participants made either: (1) gender discriminations based on the face; (2) case judgments based on the words; or (3) syllable number judgments based on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

15
133
4
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(153 citation statements)
references
References 52 publications
15
133
4
1
Order By: Relevance
“…In recent years, the neural effects of task load on processing of emotional stimuli have begun to receive more systematic attention. Several studies have demonstrated that activity in emotion processing regions of the brain in response to negative emotional stimuli, such as the amygdalae, depend on the availability of attentional resources for processing of these stimuli Erk et al, 2007;OkonSinger et al, 2007;Mitchell et al, 2007;Pessoa et al, 2002;Van Reekum et al, 2007). For example, in one study, negative visual distracters engaged the amygdalae during participants' judgements whether two bars were like oriented or not (Pessoa et al, 2002), but only when the difference in orientation of two bars was easy to judge.…”
mentioning
confidence: 99%
“…In recent years, the neural effects of task load on processing of emotional stimuli have begun to receive more systematic attention. Several studies have demonstrated that activity in emotion processing regions of the brain in response to negative emotional stimuli, such as the amygdalae, depend on the availability of attentional resources for processing of these stimuli Erk et al, 2007;OkonSinger et al, 2007;Mitchell et al, 2007;Pessoa et al, 2002;Van Reekum et al, 2007). For example, in one study, negative visual distracters engaged the amygdalae during participants' judgements whether two bars were like oriented or not (Pessoa et al, 2002), but only when the difference in orientation of two bars was easy to judge.…”
mentioning
confidence: 99%
“…Previous work has shown that emotional stimuli cause greater interference than neutral stimuli Erthal et al, 2005;Harris & Pashler, 2004;Mitchell et al 2006Mitchell et al ,2007Pessoa et al, 2003;Vuilleumier et al, 2001). This is thought to reflect reciprocal connections between the amygdala and temporal and occipital cortex; the amygdala augments the activation of sensory representations of emotional distracters within occipital and temporal cortex LeDoux, 1996;Mitchell et al, 2007;Pessoa et al, 2002;Vuilleumier et al, 2004).…”
Section: Introductionmentioning
confidence: 98%
“…This is thought to reflect reciprocal connections between the amygdala and temporal and occipital cortex; the amygdala augments the activation of sensory representations of emotional distracters within occipital and temporal cortex LeDoux, 1996;Mitchell et al, 2007;Pessoa et al, 2002;Vuilleumier et al, 2004). Indeed, this augmentation of the sensory representations of emotional stimuli by the amygdala appears to allow the enhanced perception of emotional, relative to neutral, stimuli following target stimuli in attentional blink paradigms (Anderson & Phelps, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations